MEMBANGUN KARAKTER SISWA MELALUI MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION BERBANTUAN LKS BERPENDEKATAN SCIENTIFIC MATERI KALOR DAN PERUBAHAN WUJUD (UPEJ Unnes Physics Education Journal, 2017)
Indonesia need strategy to overcome the crisis of character, one of which is through the integrated character education. The purpose of this research is to know the implementation of PBI model that helped by worksheets with scientific approach, the increasing of knowledge learning result, the developing of character, and the increasing of skill learning result,. The method that used in this research is pre experimental with Pre-test and Post-test Group design. This research results show that implementation of PBI that helped by phisics worksheets with scientific approach can improve learning outcomes of knowledge in medium category, it can also develop character especially honesty, discipline, curiosity, and communicative, and improve skills learning outcomes in medium category.